Association between Selected Indices of Adiposity and Lung Performance in Children with Cerebral Palsy (2015)
Children with cerebral palsy (CP) have mobility impairments which may lead to problems with body weight. Increased body weight or adiposity may result in respiratory dysfunction. This study investigated the relationship between indices of adiposity and lung performance in children with CP in Ibadan, Nigeria. Twenty-four children with CP participated in this ex-post facto study. Anthropometric and spirometric parameters were measured following standard procedures. Data were summarized using descriptive statistics and analysed using the Pearson's Product Moment Correlation at p = 0.05. Body mass index (BMI) was not significantly related (p > 0.05) to the indices of lung performance measured, but subscapular skinfold (SSF) thickness was significantly related with chest excursions at the 4th (r=-0.43) and 9th (r=-0.42) ribs. Quadriceps skinfold thickness (QST) was also significantly related with chest excursions at the 4th (r=-0.61), 7 (r = -0.60) and 9th (r = -0.50) ribs and the respiratory rate (p=0.03) but not with FVC, FEV, FEV/FVC and PEF (p > 0.05). This study demonstrated that increased adiposity is associated with decreased respiratory excursion in children with CP. Therapeutic intervention for children with CP should include components aimed at controlling obesity.